2012
DOI: 10.5539/jas.v4n5p131
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of GF 677 Rootstock

Abstract: The aim of this investigation was to study micropropagation of Almond GF rootstock on in vitro. Explants were cultured in MS medium containing 5 concentrations of 6-Benzylaminoporine (BAP) 0.1, 0.6, 1, 1.5 and 2 mg 1 -1 along with control treatment. Each treatment includes 5 replications. After 5 weeks of culture, the results showed that the number and length of shoots in treatment containing 1 mg 1 -1 BAP was more than the other treatments and control. The number of shoot that was obtained in treatment of 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
3
6
1
Order By: Relevance
“…These results are conformed with the results reported by Nazary Moghaddam Aghaye et al [32] in GF677 micropropagation, which suggested that BAP is more suitable for shoot multiplication of GF677. Our results showed that callus was significantly affected by medium and cytokinin type so that increasing concentrations of BAP and BA in culture medium brought about a significant enhancement in the callus weight in both experiments.…”
Section: Ba Concentrationsupporting
confidence: 96%
See 4 more Smart Citations
“…These results are conformed with the results reported by Nazary Moghaddam Aghaye et al [32] in GF677 micropropagation, which suggested that BAP is more suitable for shoot multiplication of GF677. Our results showed that callus was significantly affected by medium and cytokinin type so that increasing concentrations of BAP and BA in culture medium brought about a significant enhancement in the callus weight in both experiments.…”
Section: Ba Concentrationsupporting
confidence: 96%
“…Our results are in agreement with those of Unek et al [10] on G · N15 (Garnem) that MS medium containing BAP was the best medium for proliferation of garnem. In contrast to our results, earlier, for G · N9, WPM and QL were found to have a better effect on shoot proliferation rate than either MS or ½ MS medium and the possible explanation given for this was the reduced nitrogen content in WPM [13] Although Nazary Moghaddam Aghaye et al [32] and Molassiotis et al [3] reported that for GF677, use of MS resulted in the best shoot proliferation rates. Dejampour et al [21] found that, the use of DKW resulted in the best proliferation rate.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations